(untitled) (BioLaw Journal - Rivista di BioDiritto, 2026)
This study analyses the more than quarter-century case-law journey on the “fundamental right to a dignified death” of the Colombian Constitutional Court. It opens with the exam of the birth of the right in 1997 and then explores how, over more than two decades, the Constitutional Court has progressively defined its nature and scope. Finally, it examines the first extension of the clinical cases that qualify for medically assisted death, as well as the definitive elimination of an incomprehensible inconsistency: how the decriminalisation of euthanasia under certain conditions has coexisted with the absolute prohibition of assisted suicide for 25 years.